Thai Student Teacher Learning Innovation: A Second-Order Confirmatory Factor Analysis - Achah Binheem; Paitoon Pimdee; Sirirat Petsangsri (TEM Journal, 2021)
The study’s objective was to analyze the corroborating elements of a Thai student teacher’s (TST) learning innovation as perceived through the expertise of their teachers. Therefore, from 12 Thai teaching universities (Rajabhats) located across four Thai regions, multiple sampling techniques were used to select a sample of 151 teaching professionals. The research instrument was a questionnaire using a 5-level scale to assess the opinions on the four latent and 12 observed variables. The results showed that of the three latent variables analyzed that contributed to TST learning innovation (IN), learning innovation use (US) were perceived as most important, followed by the learning innovation development process (DE) and then the TST’s creative collaboration (CO) abilities, respectively. Finally, all the observed variables were determined to be compatible with TST innovation learning at a ‘high’ level.
Keywords: Evaluation of Teaching Practices; Communication in Education and Healthcare; Educational Environments and Student Outcomes